2018
DOI: 10.1016/j.jddst.2017.11.021
|View full text |Cite
|
Sign up to set email alerts
|

Selection of phospholipids to design liposome preparations with high skin penetration-enhancing effects

Abstract: The objective of the present study is to search for a good selection method of phospholipids to design liposome preparations with high skin penetration-enhancing effects.Five kinds of phosphatidylcholines and phosphatidylglycerols each were selected. First, phospholipid aqueous dispersions and liposomes containing caffeine as a model drug were tested for their skin penetration-enhancing effects using excised hairless rat skin. As results, 1,2-distearoyl-sn-glycero-3-phosphocholine (DSPC) and 1,2-dipalmitoyl-sn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 23 publications
(23 reference statements)
0
12
0
1
Order By: Relevance
“…The choice of design parameters was determined by previously reported studies. The type of phospholipids used has been investigated in several studies and has been reported to produce liposomal vesicles with different properties . Therefore, natural and synthetic phospholipids (EPC and DMPC) were investigated in this study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The choice of design parameters was determined by previously reported studies. The type of phospholipids used has been investigated in several studies and has been reported to produce liposomal vesicles with different properties . Therefore, natural and synthetic phospholipids (EPC and DMPC) were investigated in this study.…”
Section: Resultsmentioning
confidence: 99%
“…The type of phospholipids used has been investigated in several studies and has been reported to produce liposomal vesicles with different properties. [28] Therefore, natural and synthetic phospholipids (EPC and DMPC) were investigated in this study. Additionally, it was reported that the surfactant type and concentration can also affect transfersome size and % EE.…”
Section: Transfersome Optimisation and Taguchi Doe Analysismentioning
confidence: 99%
“…Size is an essential factor to bear in mind since smaller sizes lead to larger surface areas and subsequently to greater reactivity and control the drug's release kinetics (Samadi et al, 2020 ). According to Sakdiset et al ( 2018 ), composition and design are essential factors to consider for developing efficient nanoliposome with high skin permeation and improved performance. The research group found that 1,2-di- palmitoyl-sn-glycero-3-phosphoglycerol, sodium salt (DPPG) can be a promising phospholipid candidate for nanoliposome formulations with high skin penetration-enhancing effects.…”
Section: Influencing Factors That Affect the Nanoliposomes Performancmentioning
confidence: 99%
“…It has been many times shown that the nature of liposomes strongly in uences the behavior of incorporated molecules [35][36][37][38] . There are many reports showing the effect of tocopherols in pure lipid systems 11,21,39 .…”
Section: Antioxidant Activity Of Tocochromanols In Different Nanocarrmentioning
confidence: 99%